Impact of Flash Sale Promotions and Brand Ambassadors on E-commerce Purchasing Decisions: A Study of Indonesian Consumers: Dampak Promosi Flash Sale dan Brand Ambassador terhadap Keputusan Pembelian E-commerce: Studi pada Konsumen Indonesia - Rahma , Bella Aulia; Purwanto, Nuri (Indonesian Journal of Law and Economics Review, 2023)
This study employs an explanatory research method to investigate the influence of Flash Sale Promotions and Brand Ambassadors on purchasing decisions in the context of e-commerce, focusing on Indonesian consumers. Data collected from 100 questionnaires distributed to users of e-commerce applications reveal that effective Flash Sale Promotions positively impact purchasing decisions, indicating that the quality of such promotions is directly correlated with higher purchase decisions within e-commerce applications. Additionally, the presence of compelling Brand Ambassadors is found to enhance purchasing decisions on the Shopee e-commerce application, with improved ambassador performance leading to increased purchasing decisions. These findings underscore the significance of strategic marketing approaches, such as Flash Sale Promotions and Brand Ambassador programs, in shaping consumer behavior in the e-commerce sector. Highlights: Flash Sale's Impact: Examining the influence of Flash Sale Promotions on e-commerce purchasing decisions. Brand Ambassador Effect: Investigating the role of Brand Ambassadors in shaping consumer behavior. Indonesian Market: Focusing on the specific context of Indonesian consumers in the e-commerce landscape. Keywords: E-commerce, Flash Sale, Brand Ambassadors, Purchasing Decisions, Indonesian Consumers